Metamizole outperforms meloxicam in sepsis: insights on analgesics, survival and immunomodulation in the peritoneal contamination and infection sepsis model - Liu, Na; Sonawane, Mitali; Sommerfeld, Oliver; Svensson, Carl-Magnus; Figge, Marc Thilo; Bauer, Reinhard; Bischoff, Sabine Juliane; Bauer, Michael; Osuchowski, Marcin Filip; Press, Adrian Tibor (Frontiers in Immunology, 2024)
Background: Limited availability and side effects of opioids have led to an increased use of non-opioid analgesia in animal disease models. However, by affecting the immune-inflammatory reactions, analgesia may disrupt the resolution of the host inflammation and modulate the survival in septic animals. This study used a clinically relevant sepsis mouse model of peritoneal contamination and infection (PCI) to investigate the antinociceptive and anti-inflammatory properties of two non-opioid analgesics.Methods: Adult C57BL/6J mice were intraperitoneally injected with a human feces suspension and received either no analgesics (Non-A), Meloxicam, or Metamizole orally. The mice were monitored for pain and illness. Mortality was assessed at 7 days post-PCI. A separate group of mice was sacrificed 24 hours after infection. Blood, peritoneal lavage fluid (PLF), liver, and spleen were harvested for pathogen load quantification via qPCR, macrophage phenotyping, neutrophil infiltration/activation, and systemic/tissue cytokine release by flow cytometry.Results: Meloxicam but not Metamizole reduced the mortality of septic mice by 31% on day 7 compared to the Non-A group. Both analgesics effectively alleviated pain but did not affect illness severity, body weight, and temperature. Meloxicam quadrupled the bacterial burden in the blood and PLF. In high IL-6 responders, Meloxicam treatment was associated with reduced circulating IL-10 and IL-1 compared to the Non-A septic group. In low IL-6 responders, Meloxicam increased circulating MCP-1 levels and decreased PGE2 levels compared to Non-A septic mice. Notably, Meloxicam reduced spleen neutrophil infiltration by 20% compared to two other sepsis groups.Conclusions: Metamizole and Meloxicam effectively relieved pain and increased the animals' basal activity in the PCI sepsis model. Meloxicam prolonged survival yet triggered maladaptive responses due to its immunosuppressive features that decreased tissue bacterial clearance during sepsis. In contrast, Metamizole constitutes a safe and effective non-opioid alternative for analgesic control in the non-surgical PCI sepsis model.